Pengaruh Pemberian Latihan Fisik PEOL Selama Hemodialisis Terhadap Fatigue Pada Pasien Gagal Ginjal Stadium Akhir - Amilia, Yunita; Istibsaroh, Faridatul; Suryadi, Mohammad Shiddiq; Bakar, Abu; Nadatien, Ima (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Background: End-stage renal failure patients undergoing hemodialysis experience various comorbid conditions, social, psychological, financial stress, medication, symptoms that these patients often experience are closely related and can lead to fatigue problems and affect the assessment of the quality of life.Objective: To identify the effect of giving PEOL physical training during hemodialysis on fatigue in final stadium renal failure patientMethods: This article used a quasy experimental with pre and post-test and use a control group design approach. The sample in this study was 32 respondents divided into 16 interventions group and 16 control groups. The sampling technique is simple random sampling by using a lottery. Data collection was obtained by using a questionnaire Chalder Fatigue Scale. Data analysis is used paired t-test and Independent t-test with a confidence level of 95% (α=0,05)Results: The results of data analysis using the paired t-test showed the results of p-0,002 and the independent t-test showed the results of p = 0,000Conclusion: PEOL physical training during hemodialysis can reduce fatigue in final stadium renal failure patients